2023
DOI: 10.1371/journal.pone.0280649
|View full text |Cite
|
Sign up to set email alerts
|

Gene expression profiling of the masticatory muscle tendons and Achilles tendons under tensile strain in the Japanese macaque Macaca fuscata

Abstract: Both Achilles and masticatory muscle tendons are large load-bearing structures, and excessive mechanical loading leads to hypertrophic changes in these tendons. In the maxillofacial region, hyperplasia of the masticatory muscle tendons and aponeurosis affect muscle extensibility resulting in limited mouth opening. Although gene expression profiles of Achilles and patellar tendons under mechanical strain are well investigated in rodents, the gene expression profile of the masticatory muscle tendons remains unex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 42 publications
0
3
0
Order By: Relevance
“…Yumoto et al [ 21 ] reported differences in gene expression between temporal tendons from patients with MMTAH and temporal tendons from patients with facial deformity. Ito et al [ 20 ] reported differences in gene expression among the masseter aponeurosis, temporal tendon, and Achilles tendon from Japanese macaque. Although there was no overlap between our candidate genes and the genes reported by Yumoto et al [ 21 ], future analysis using samples from our patients could determine whether six genes ( Mkx , Myf5 , MyoD , ANKRD2 , TNNT1 , MYH7 ) reported by Yumoto et al were upregulated in temporal tendon from our patients with MMTAH.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Yumoto et al [ 21 ] reported differences in gene expression between temporal tendons from patients with MMTAH and temporal tendons from patients with facial deformity. Ito et al [ 20 ] reported differences in gene expression among the masseter aponeurosis, temporal tendon, and Achilles tendon from Japanese macaque. Although there was no overlap between our candidate genes and the genes reported by Yumoto et al [ 21 ], future analysis using samples from our patients could determine whether six genes ( Mkx , Myf5 , MyoD , ANKRD2 , TNNT1 , MYH7 ) reported by Yumoto et al were upregulated in temporal tendon from our patients with MMTAH.…”
Section: Discussionmentioning
confidence: 99%
“…To elucidate the environmental factors of this disease, Hayashi et al [ 18 , 19 ] examined the effect of cyclic stretch on tenocytes and found that the expression of CRYBA4 mRNA was increased and the abundance of the decorin protein was increased via the yes-associated protein. Recently, Ito et al [ 20 ] showed that the response to mechanical stretching stress was different in the temporal tendon and the Achilles tendon. Yumoto et al [ 21 ] found that gene expression was different in the temporal tendon of patients with MMTAH and in the temporal tendon of patients with jaw deformity by RNA-seq.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation